2022
DOI: 10.1177/00846724221126755
|View full text |Cite
|
Sign up to set email alerts
|

Cultural dimensions of nonsuicidal self-injury: A Malaysian perspective

Abstract: Self-injury is a perilous and increasingly common behavior that is particularly prevalent among youth. Nonetheless, there is a deep-rooted public stigma towards people who self-injure. Consequently, people who engage in self-injury are reluctant to seek professional help or disclose their experiences to others. This article aims to combat stigma and promote help-seeking behavior by debunking the common myths surrounding self-injury in the Malaysian context. Specifically, this article aims to serve as an eye-op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Legally, the move to decriminalize suicide attempts has the potential to encourage more help-seeking behavior. Religiously, Fernandez and colleagues argue that all primary religions in Malaysia disprove self-injury and instead encourage them to seek professional help ( 29 ), while another study has shown religiosity providing a positive effect on resilience and self-efficacy ( 30 ). Further studies may be required to address this issue from the NSSI point of view.…”
Section: Introductionmentioning
confidence: 99%
“…Legally, the move to decriminalize suicide attempts has the potential to encourage more help-seeking behavior. Religiously, Fernandez and colleagues argue that all primary religions in Malaysia disprove self-injury and instead encourage them to seek professional help ( 29 ), while another study has shown religiosity providing a positive effect on resilience and self-efficacy ( 30 ). Further studies may be required to address this issue from the NSSI point of view.…”
Section: Introductionmentioning
confidence: 99%